S
N
=
k
=
1
∑
N
k
1
Let S N satisfy the equation above. What is the value of n → ∞ lim ( S 2 n − S n ) ?
Give your answer to three decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Recall S N ∼ ln N . Hence, we have
n → ∞ lim S 2 n − S n = n → ∞ lim ln ( n 2 n ) = ln 2
S 2 n − S n = ∑ r = 1 n ( 2 n − 1 1 + 2 n 1 − n 1 ) = ∑ r = 1 n ( 2 n − 1 1 − 2 n 1 )
lim n → ∞ ( ∑ r = 1 n ( 2 n − 1 1 − 2 n 1 ) ) = lo g e 2
n → ∞ lim S 2 n − S n = n → ∞ lim i = 1 ∑ n n + i 1 = n → ∞ lim n 1 i = 1 ∑ n ( 1 + n i ) 1
= ∫ 0 1 1 + x 1 d x = ln 2
Log in to reply
Nice approach. And by the same reasoning we would have
lim n → ∞ ( S b n − S a n ) = ln ( a b ) for integers b ≥ a ≥ 2 .
We see that S n = 1 1 + 2 1 + 3 1 + . . . + n 1 . . . . . . ( A ) Similarly, S 2 n = 1 1 + 2 1 + 3 1 + . . . + n 1 + n + 1 1 + n + 2 1 + . . . + 2 n 1 . . . . . . ( B ) Subtract the above two to get: S 2 n − S n = n + 1 1 + n + 2 1 + n + 3 1 . . . + 2 n 1 We need to find: n → ∞ lim S 2 n − S n The problem can now be neatly written as: S = n → ∞ lim r = 1 ∑ n n + r 1 Or, S = n → ∞ lim n 1 r = 1 ∑ n 1 + n r 1 Now make the substitution- n r → x and n 1 → d x So now we have S = ∫ 0 1 1 + x 1 d x Or, S = ln ( 2 ) = 0 . 6 9 3
I'll add some background and comments to the solution.
The sum S n is usually known as the n -th harmonic number, denoted by H n . The asymptotic behavior of H n is well-known, which follows from the fact that H n ∼ ∫ 1 n x 1 d x = lo g ( x ) , where lo g ( x ) is the napierian logarithm. In fact, the limit n → ∞ lim ( H n − lo g ( n ) ) exists and equals γ , the Euler-Mascheroni constant . The fact that the sequence H n − lo g ( n ) is convergent can be easily shown, first proving that it is bounded, and then proving that it is decreasing.
Therefore, n → ∞ lim ( S 2 n − S n ) = n → ∞ lim ( γ + lo g ( 2 n ) − γ − lo g ( n ) ) = lo g ( 2 ) . Moreover, we can also notice that in general, if k is a positive integer, n → ∞ lim ( S k n − S n ) = n → ∞ lim ( γ + lo g ( k n ) − γ − lo g ( n ) ) = lo g ( k ) . As a matter of fact, this problem admits an easy generalization. Let { a n } n = 1 ∞ and { b n } n = 1 ∞ two sequences of positive integers such that diverge to ∞ , and n → ∞ lim b n a n = L exists. Then n → ∞ lim ( S a n − S b n ) = lo g ( L ) . As a curious example, n → ∞ lim ( S ⌊ n ! e n ⌋ − S ⌊ n n n ⌋ ) = lo g ( 2 π ) , where ⌊ x ⌋ is the floor function. This follows from Stirling's approximation .
Let B n = S 2 n − S n = ∑ x = n + 1 2 n x 1 . We will determine the value of lim n → ∞ B n using the Squeeze Theorem (for sequences). We also define A n , C n like this: A n C n = ∫ x = n + 1 2 n + 1 x 1 d x = ∫ x = n 2 n x 1 d x . Since x 1 is strictly decreasing for x > 0 , by evaluating the integral for A n using a left Riemann sum with n intervals, we get the following inequality: ∫ x = n + 1 2 n + 1 x 1 d x ≤ x = n + 1 ∑ 2 n x 1 . Similarly, using a right Riemann sum with n intervals to evaluate the integral for C n we get the following inequality: ∫ x = n 2 n x 1 d x ≥ x = n + 1 ∑ 2 n x 1 . Putting these together we get that A n ≤ B n ≤ C n . But we can also evaluate A n , C n directly by integrating, giving us: A n C n = lo g ( 2 n + 1 ) − lo g ( n + 1 ) = lo g ( n + 1 2 n + 1 ) = lo g ( 2 − n + 1 1 ) = lo g ( 2 n ) − lo g ( n ) = lo g 2 . Therefore, we have the following inequality: lo g ( 2 − n + 1 1 ) ≤ S 2 n − S n ≤ lo g 2 . Therefore, by the Squeeze Theorem we have: n → ∞ lim S 2 n − S n = lo g 2 .
Problem Loading...
Note Loading...
Set Loading...
(To the author: The standard notation for those is H n . They are called harmonic numbers .)
In any case, we have S 2 n − S n = 1 − 2 1 + 3 1 − ⋯ − 2 n 1 . Proof:
Letting n go to infinity, we get the familiar infinite series 1 − 2 1 + ⋯ = ln 2 .